Aspects of vineyard vegetation in Northeastern Italy and eastern neighbouring territories: Cerastio tenoreani-Geranietum dissecti and Mercurialetum annui as archaic, disappearing coenosis - Poldini, Livio; Tasinazzo, Stefano (Hacquetia, 2019)
Recent original data concerning vineyard spring vegetation from Veneto hilly belt (Northeastern Italy) highligthed once again the phytogeographic originality of southeastern territories with respect to Central European ones, also in anthropogenic coenosis. New relevés suggested to restate the association Cerastio tenoreani-Geranietum dissecti as vicarious vegetation of Geranio rotundifolii-Allietum vinealis occurring on the north side of the Alps. The comparison of autumn material from terracing vineyards of the sandy-marly Eocene flysch around Trieste coast with similar European relevés enabled to reject the not validly described Anagallido-Mercurialetum and to replace it with Mercurialetum annuae. In modern winegrowing Cerastio-Geranietum and Mercurialetum annuae are vanishing due to changing of agronomic schemes, as some relevés reported in the text document.